Avaliação de severidade quanto à resistência ao crestamento bacteriano comum em painel de feijões carioca - Barbosa, Caio Cesar Ferrari (Universidade Federal de São Carlos, 2021)
The common bean (Phaseolus vulgaris L.) is one of the most important components of the Brazilian diet, as it is an excellent source of protein, and the incidence of diseases is one of the most important factors that affect its productivity. Common bacterial blight (CBC) is the main bacterium that affects this crop. Symptoms of BCC are observable throughout the plant, affecting from the seeds to the leaves. Tissue infection occurs through natural openings such as stomata and wounds. In this experiment, leaf incisions were made with scissors previously sterilized on the two primary leaves. Lesions are characterized by flabby tissue and surrounded by a narrow lemon-yellow ring. Resistance to BCC in common bean is a complex and quantitative characteristic, resulting from the interaction of several genes. The objective was to evaluate the severity of resistance of BCC disease using a Xanthomonas axonopodis pv. Phaseoli (Xap 19) in a diversity panel of 149 bean genotypes from Rio de Janeiro. The experiment was carried out in a greenhouse, with seeds planted in 800ml pots with substrate. The experimental design was of 3 randomized blocks, with 149 treatments used, with 3 replications for each variety (149x3). The inoculation took place 10 days after planting the seeds and the evaluation was carried out 10 days after inoculation (total of 20 days). For statistical analysis, the Scott-Knott test was used. At the end of the project, the results were obtained that 85% of the genotypes were considered susceptible and only 15% moderately resistant, taking into account the severity parameter developed by RAVA in 1984 and the statistical analysis of the Scott-Knott test, was possible to conclude that there was a significant difference between the treatments.
Severity assessment as to resistance to common bacterial breast in common beans
Keywords: Crestamento bacteriano comum (CBC); Phaseolus vulgaris L; Xanthomonas axonopodis pv. phaseoli; CIENCIAS AGRARIAS::AGRONOMIA::FITOSSANIDADE; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA